Rejection Sensitivity Mediates the Relationship Between Social-Interpersonal Stressors and Depressive Symptoms in Military Context - Wang, Jia; Cheng, Xiaotong; Xu, Ke; Xu, Huimin; Wang, Huizhong; Feng, Zhengzhi (Frontiers in Psychiatry, 2020)
Background: Depression is pervasive in the military context and is likely to elicit lasting negative effects on health. Based on interpersonal models, social-interpersonal stressors are significantly associated with the development and maintenance of depression. However, little is known about the mechanisms by which these stressors increase the risk of depression in terms of social relationships. Rejection sensitivity, which refers to people who are sensitive to social rejection and tend to anxiously expect, readily perceive, and overreact to it, may play an underlying role in this process, as it is formed through social-interpersonal stressors and then aggravates further symptoms of depression. Objectives: The current study aimed to examine the mediating effects on the relationship between social-interpersonal stressors and depressive symptoms in the military context. Methods: This study recruited 600 soldiers aged from 17-36 (M = 21.80; SD = 2.99; 100% males) with a cluster sampling method who completed Social-Interpersonal Stressors subscale, Rejection Sensitivity Questionnaire (RSQ) and Self-Rating Depression Scale (SDS). Mediation analyses examined the underlying mechanism between social-interpersonal stressors and depressive symptoms. Results: The results support the hypothesis and indicate that rejection sensitivity mediates the association between social-interpersonal stressors and depressive symptoms (B indirect = 0.02, p < 0.001, 95% CI= 0.005 to 0.044). Conclusions: The findings suggest that interventions designed to desensitize individuals’ high levels of rejection sensitivity may help to decrease their risk of depressive symptoms in the military environment. Rejection sensitivity is an important mechanism underpinning the development of depressive symptoms. Other theoretical and applied implications for prevention of depressive symptoms in the military context are discussed.